The Accuracy of the CBCT‐Based 3‐Dimensional Replica of the Donor Tooth in Autotransplantation - Jessica Juslin; Tuija Teerijoki‐Oksa; Päivi Jääsaari; Marja Ekholm; Pekka Vallittu; Lippo Lassila; Hanna Thorén (Clinical and Experimental Dental Research)
ABSTRACT Background This study evaluated the accuracy of the CBCT reconstruction model compared to the natural tooth and the accuracy of the replica tooth compared to the natural tooth. Objective The hypothesis was that a replica tooth could be used as a surgical guide in autotransplantation. Methods Three teeth were chosen and a CBCT reconstruction model was formed from each tooth. STL‐data was transferred to a milling machine and replica teeth were milled from PEEK. A digitized surface model was prepared from the natural and the replica teeth by a stereophotogrammetry scanner. The surface model from the optical scan of the natural tooth was compared to the CBCT reconstruction model and the surface model of the replica tooth. The models were matched on each other, and surface‐based rigid registration was performed between the surface models. Distances were calculated and visualized by MATLAB. Results The CBCT reconstruction model and the natural tooth were compared. The largest euclidean distance was found at the root tip in the premolar (0.93 mm) and at the furcation area in the molar (2.3 mm). When the natural tooth and the replica tooth were compared, the largest euclidean distance was found at the root tip in the premolar (1.5 mm) and at the furcation area in the molar (1.9 mm). Conclusion A CBCT scan maintains sufficient image quality for tooth autotransplantation planning. The replica tooth corresponded in size and shape to the natural tooth in terms of clinically expected need of precision.